Fractais no ensino médio: uma sequência didática - Adami, Paulo Sérgio (2013)
The intention of this dissertation is to describe a didactic sequence which aims at giving conditions to students so they are able to construct notions about the applications of fractal geometry and dynamical systems, aiding them in realizing the importance of mathematics to the development of the most diverse fields of human knowledge. Mathematics, so often emphasized in classrooms, privileges its procedural aspect, forcing the student not to perceive it as a dynamic science, linked to the comprehension of phenomena in the several fields of knowledge. Euclidean Geometry, thoroughly advertised, is, in general, more appropriate to the study of shapes found in houses, bridges and machine constructions among others, and the student might be taken to assume that mathematics is distant from the shapes observed beyond the windows of the classroom, such as in clouds, trees, rays that cut the skies and so on.